Synthesis of new disulfonamides from different substituted diamino pyridines - Behmadi, Hossein; Saadati, Seyed Mahdi; Roshani, Mina; Ghaemy, Mousa (Eclética Química, 2009)
A series of novel disulfonamide derivatives were synthesized and characterized by FT-IR, 1H NMR and MS techniques. In order to prepare new disulfonamides, at first we synthesized new diamines containing a pyridine ring. Then, they have been reacted with sulfonyl chlorides to give corresponding disulfonamides.